Destabilizing Financial Advice: Evidence from Pension Fund Reallocations - Da, Zhi; Larrain, Borja; Sialm, Clemens; Tessada, José (Review of Financial Studies, 2018)
We document a novel channel through which coordinated trading exerts externalities on financial markets. We study the impact of a financial advisory firm that recommends frequent reallocations between equity and bond funds to Chilean pension investors. The recommendations generate large and coordinated fund flows that are exacerbated by the strategic complementarity arising from fund trading restrictions. The recommendations generate significant price pressure and increased volatility in the stock market. In response to these large trade flows, pension funds shift their allocations to more liquid securities. Our findings suggest that giving retirement savers unconstrained reallocation opportunities can destabilize financial markets. Received March 11, 2016; editorial decision July 8, 2017 by Editor Itay Goldstein.